2018
DOI: 10.3390/chemosensors6040049
|View full text |Cite
|
Sign up to set email alerts
|

Super Stable Pollution Gas Sensor Based on Functionalized 2D Boron Nitride Nanosheet Materials for High Humidity Environments

Abstract: We report on studies of new gas sensing devices to be used in high humidity environments. Highly thermal-stable, super hydrophobic 2-dimensional (2D) boron nitride nanosheets (BNNSs) functionalized with Pt nanoparticles were prepared and used as an active layer for the prototype. The morphologic surface, crystallographic structures and chemical compositions of the synthesized 2D materials were characterized by using optical microscope, scanning electron microscope (SEM), transmission electron microscope (TEM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 47 publications
(57 reference statements)
0
2
2
Order By: Relevance
“…Furthermore, the abundant nitrogen and/or boron vacancies (V N or V B ) in the defective structure of hBN could have acted as electron capture sites upon exposure to either acetone or ethanol [45,46], thereby resulting in improved sensitivity. Interestingly, regardless of the theoretical studies showing that the even, smooth surfaces of hBN nanosheets enabled full access of their atoms to the adsorbing gas molecules, thus allowing for larger sensor area per unit volume and improving the sensitivity [25][26][27], our results showed that the formation of well-defined morphology hBN nanosheets greatly hindered their performance towards the detection of volatile organic compounds. In summary, the results indicated that our synthesised hBN nanosheets are potential candidates for room temperature chemoresistive gas sensors (Table 2), as the obtained values were comparable to those of graphene, conductive metal oxides, mxenes, as well as transition metal dichalcogenides (TMDs) [25].…”
Section: Determination Of Sensing Parameterscontrasting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, the abundant nitrogen and/or boron vacancies (V N or V B ) in the defective structure of hBN could have acted as electron capture sites upon exposure to either acetone or ethanol [45,46], thereby resulting in improved sensitivity. Interestingly, regardless of the theoretical studies showing that the even, smooth surfaces of hBN nanosheets enabled full access of their atoms to the adsorbing gas molecules, thus allowing for larger sensor area per unit volume and improving the sensitivity [25][26][27], our results showed that the formation of well-defined morphology hBN nanosheets greatly hindered their performance towards the detection of volatile organic compounds. In summary, the results indicated that our synthesised hBN nanosheets are potential candidates for room temperature chemoresistive gas sensors (Table 2), as the obtained values were comparable to those of graphene, conductive metal oxides, mxenes, as well as transition metal dichalcogenides (TMDs) [25].…”
Section: Determination Of Sensing Parameterscontrasting
confidence: 56%
“…Interestingly, regardless of the theoretical studies showing that the even, smooth surfaces of hBN nanosheets enabled full access of their atoms to the adsorbing gas molecules, thus allowing for larger sensor area per unit volume and improving the sensitivity [25][26][27], our results showed that the formation of well-defined morphology hBN nanosheets greatly hindered their performance towards the detection of volatile organic compounds. In summary, the results indicated that our synthesised hBN nanosheets are potential candidates for room temperature chemoresistive gas sensors (Table 2), as the obtained values were comparable to those of graphene, conductive metal oxides, mxenes, as well as transition metal dichalcogenides (TMDs) [25]. Moreover, the sensors were found to be stable even after 18 months of storage as approximately 75%, 50%, 92%, and 8% decreases in sensor responses were observed for 0 wt %, 2.5 wt %, 5 wt %, and 10 wt % modified hBN samples after exposure to 160 ppm of acetone (Figure S7).…”
Section: Determination Of Sensing Parameterscontrasting
confidence: 56%
See 1 more Smart Citation
“…2D materials exhibit many peculiar properties, such as tunable band gap [2], controllability of spin degrees of freedom and valley degrees of freedom [3,4], etc. Due to its larger specific surface area, more adsorption sites, excellent electrical conductivity and other advantages, and its synthesis, stability, manufacturing costs and other aspects of continuous optimization and improvement, 2D materials as the representative of the gas sensor will be able to achieve miniaturization, low power consumption and other goals [5][6][7][8]. PbE(E = S, Se, Te) semiconductor nanomaterials of the sulfur genus of lead are characterized by low cost and elemental abundance.…”
Section: Introductionmentioning
confidence: 99%